Normal development of the dentition - Linden, Frans P. G. M. van der, 1932-; Dentaurum (Firm) (Berlin, Germany : Quintessenz Verlag ; Ispringen, Germany : Dentaurum, 2000)
(Producer) Describes and illustrates the morphogenesis of the teeth with extensive new animated material. Shows variations in the arrangement of teeth at subsequent stages of development that still lead to normal occlusion. Explains the relationship of tooth development to the size of the jaws and to subsequent skeletal growth. Elucidates associated abnormal conditions that occur
Authors, Frans P.G.M. van der Linden, Ralf J. Radlanski, James McNamara, Jr. ; scientific contributions, Rainer R. Miethke, et al ; script, Frans P.G.M. van der Linden, Ralf J. Radlanski, James A. McNamara, Jr.
Keywords: Tooth -- growth & development; Dentition; Tooth -- embryology